“Monitoring Implementation Financing Murabahah PT. Bank Tabungan Negara, Tbk. Sharia Branch Malang” - Mohamad Faiz; Lutfi Harris (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research have done at PT. Bank Tabungan Negara Tbk. Syariah Malang with the title “Monitoring Implementation Financing Murabahah PT. Bank Tabungan Negara, Tbk. Sharia Branch Malang”. The goal of this research are to know the giveaway procedure of murabahah financing at PT. Bank Tabungan Negara Tbk. Syariah Malang and to know the implementation of monitoring murabahah financing at PT. Bank Tabungan Negara Tbk. Syariah Malang. The first step have done by writer are fixed a background of the problem an then formulate it. Data was collected by writer is seconder data. It was got from books, reports, Standart Operating Prosedur company that match with the goal of writing and with interview to staff of PT. Bank Tabungan Negara Tbk. Syariah Malang. From the seconder data writer get theory that will be analized and be evaluated so writer can give conclusion also suggestion. The result of research explain that implementation of giveaway procedure of murabahah financing is suitable with principle of syariah. The giveaway procedure of murabahah financing are, filling application form of murabahah financing by customer, Application of murabahah financing by A/M to Support Financing, BI Checking, Analyse and Taxation, continuing Analyse, yuridis Analyse, Sending the result of analyse, Preparing Commite, Decision of Commite, relationship, realization, saving the loan document. Implementation of monitoring consist of two activity. First, regular monitoring is visit the customer regularly and control paying the liability to bank every end of month. Second, Restructuring of financing was done if the financing that have given to customer to be a problem. From explanation above get the conclusion that giveaway procedure of murabahah financing and implementation of monitoring is management system of financing that have fixed by Bank.